The frequency of anemia in the elderly patient populationin Van province, Turkey. A cross-sectional study - Eker, Elif; Ekinci, Omer (My University, 2021)
Aim: This study aims to determine the prevalence and morphological distribution of anemia among elderly patients who presentedto the hospital during a certain time period.Materials and Methods: Haemogram parameters of all patients aged 60 or older who attended our hospital for any reason during acertain time period were reviewed. Anemia was defined according to the criteria by the World Health Organization (WHO). Cases of anemia were classified based on the mean corpuscular volume (MCV) results of the patients as microcytic, normocytic, or macrocytic. The prevalence and morphological classification of anemia were examined with respect to age and gender. Results: Of 1192 total patients, 608(51%) were female. The majority of the patients were in the 60–70–year range, with a rate of60.3% (718). The mean age was 69.70±7.55 years in females and 69.8±7.15 in males (p=0.680). Anemia was detected in 340 (28.5%) patients in total (24.8% in females, 32.4% in males, p=0.004). Sixty–six (19.4%) patients had microcytic anemia, 245(72.1%) had normocytic anemia, and 29 (8.5%) had macrocytic anemia. Distribution of anemia across age groups revealed 169 (23.5%) patients with anemia in the 60–70–years age group (69 (%18.2) vs 100 (%29.6), p=0.001). The prevalence of anemia was different between genders in both the 60–70–years and ?81 years groups (respectively, 52 (%14.6) vs 66 (%18.5), p=0.426 and 30 (%25.6) vs 23 (%19.7), p=0.295).Conclusion: The prevalence of anemia increases with aging. Determination of the prevalence and the etiological distribution ofanemia, particularly in the elderly patient group, may provide practical information in daily practice regarding the approach to be adopted towards patients in a certain region. We think that these results provide information on the epidemiology of anemia among elderly patients in the specified region and will contribute to future studies in this aspect.
Keywords: Genel ve Dahili Tıp; Geriatri ve Gerontoloji; Sağlık Bilimleri ve Hizmetleri